Factors Associated with Adherence to Tablet FE Consumption in Adolescents - Stellata, Alyxia Gita; Kartikawati, Sri Lestari; Yusita, Intan; Huwaida, Hasna Shafa (International Journal of Midwifery and Health Sciences, 2024)
Background: Anemia has a significant impact on people's health, especially in adolescent girls. Anemia in adolescents can inhibit psychomotor development, interfere with cognitive abilities and learning. Therefore, the problem of bleeding deficiency must be prevented and treated since adolescence with consuming blood tablets regularly. But, based on the data, there are still 4,444 adolescent girls who do not obedience and realize the importance of taking blood-added tablets as an effort to prevent anemia. Thus, this study aimed to determine the correlation between the factors that relate to the obedience of consuming Fe tablet in adolescent girls. Method: This study used observational analytics with a cross-sectional approach starting from March to July 2023 in SMAN 1 Bojongsoang. This research was conducted on 85 respondents. The data research instrument in this study used MMAS-8 questionnaire and additional questionnaire to explore the cause of disobedient of consuming Fe tablet then were analyzed by using Spearman's rho test. Result: The results showed that there was 16.5% samples with low obedience, 43.5% moderate obedience, and 40% high obedience. There was a relationship between Fe tablet’s favor with obedience of consuming Fe tablet (r -0.255, p 0.019). There was no relationship of Fe tablet t’s preferences (p 0.927), parent’s alert (0.325), teacher’s alert (0.207), inconvenience of taking Fe tablet (p 0.623), completed Fe tablet (0.547), and forgetting to take Fe tablet with obedience of consuming Fe tablet (0.988). Conclusion: There was a relationship between Fe tablet’s favor with obedience of consuming Fe tablet in adolescent girls in SMAN 1 Bojongsoang. Suggestions for education institution is to optimize the socialization about the risk of anemia and the urgency of consuming Fe tablet. Thus, for student can increase the obedience of consuming Fe tablet regularly.